FRANZISCEAN CADASTRE IN LANDSCAPE STRUCTURE RESEARCH: A SYSTEMATIC REVIEW - Dolejš, Martin; Forejt, Michal (Quaestiones Geographicae, 2019)
Historical and archival sources are of cardinal importance in landscape research addressing the processes and course of landscape changes in European regions. The Franziscean cadastre from the 19th century is among the most widely used historical sources in Central Europe. We identified 1440 records, finally providing 104 articles reporting the use of the Franziscean cadastre for in-depth analyses in order to identify (i) the practice of the cadastral data processing, (ii) purpose and spatial extent of the study, (iii) use of complementary sources and (iv) particular land use/land cover classes under study. We have found the increasing attention towards the Franziscean cadastre as a source for landscape research reflected by the doubling number of records in the past decade with majority of the case studies located in Czechia (79), followed by Austria (9) and Italy (3). We have identified the trends in the use in landscape trajectory research and application to hydrology, agriculture and forestry. As regards the data processing, several issues connected with the methodology or design of the records were found (e.g. geographic information system processing description and data source specification). We further problematize the suitability of the supplementary data used and conclude our review with a set of recommendations to contribute to the discussion on the methodology of landscape reconstruction with historical datasets.